ANALISIS KEUNGGULAN KELEMAHAN MEDIA PEMBELAJARAN DIGITAL DAN SUMBER BELAJAR DIGITAL (E-LEARNING DAN AI) - Wahdini; Dina Mariana Nasution; Mirsal Angga Sosa Nasution; Syafnan Lubis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the advantages and disadvantages of digital learning media and digital learning resources, particularly e-learning and Artificial Intelligence (AI), from the perspective of Islamic Religious Education (IRE). This research employed a library research method with a descriptive qualitative approach. The data were collected from various literature sources, including books, scientific journals, articles, and other relevant documents related to digital learning media, e-learning, AI, and Islamic Religious Education. The findings reveal that digital learning media, e-learning, and AI offer several advantages, such as improving learning effectiveness, facilitating access to information, enhancing interactivity, and supporting flexible learning without limitations of time and place. However, these technologies also present several challenges, including dependence on technology and internet access, limited learning supervision, digital distractions, unequal access to technology, and the potential misuse of information that may conflict with Islamic values. From the perspective of Islamic Religious Education, the use of digital technology and AI is permissible as long as it provides benefits and does not contradict Islamic teachings. Therefore, the implementation of technology in Islamic education should be carried out wisely, responsibly, and with due consideration to moral values, ethics, and the development of students’ Islamic character.